Evaluation of the separation and purification of 227Th from its decay progeny by anion exchange and extraction chromatography. (June 2017) - Ivanov, P.I.; Collins, S.M.; van Es, E.M.; García-Miranda, M.; Jerome, S.M.; Russell, B.C.
Abstract: Thorium-227 is currently undergoing evaluation as a potential radionuclide for targeted cancer therapy, and as such a high chemical purity of the material is required. To establish a reliable procedure for radiochemical isolation of 227 Th from the parent 227 Ac and decay progeny, which includes the radiotherapeutic 223 Ra, the performance of three different separation schemes based on ion-exchange and extraction chromatography have been evaluated. The results suggest that both ion exchange and extraction chromatographic techniques can be successfully used for the separation of 227 Th from its decay progeny, however extraction chromatographic resins demonstrate favourable performance in terms of Th recovery and purification from radionuclide impurities. Highlights: Development of a radiochemical separation of 227 Th from residual 227Ac as well as from decay progeny. Evaluation of ion-exchange and extraction chromatography techniques. TEVA resin demonstrates favourable performance in terms of Th recovery and purification. Developed method is applicable to both nuclear medicine and environmental analysis.